Pendidikan Formal Anak Dalam Perspektif Nelayan Suku Bajo di Kampung Bajo - Ikhsan, Andi Muhammad; Hasriyanti, Hasriyanti; Syarif, Erman (UNIVERSITAS NEGERI MAKASSAR, 2020)
This study aims to determine the perspective of Bajo fishermen on children's formal education, to describe the living conditions of Bajo Tribal fishermen and the factors that influence formal education for their children. This type of research is qualitative research. The subjects in this study were the Bajo Tribe fishing community and the Bajo Tribe customary leader. Data collection techniques carried out by observation, interviews, literature review and research documentation. The results of this study indicate that the Bajo tribe has fairly adequate living conditions. In addition, the livelihood of the Bajo tribe still expects a large portion of their income from marine products. The Bajo are a minority ethnic group and are closed to other tribes. The life of the Bajo tribe which had always been difficult resulted in many of their children dropping out of school. Besides they also have to help their parents at sea. So that disrupt their learning activities and even cause them to drop out of school. In terms of motivating their children to go to school, only a small portion of Bajo fishermen pay attention to their children for school. Economically and the ability of the Bajo to finance their children to go to school is still quite low. It is not education that is their main goal but how to support their families.